Optimising Electrode Montages in Conventional Transcranial Direct Current Stimulation and High-Definition Transcranial Direct Current Stimulation of the Cerebellum for Pain Modulation - Adelais Farnell Sharp; Alice Witney (Brain Sciences)
The cerebellum is involved in pain processing and, therefore, an important target for non-invasive brain stimulation (NIBS) for analgesia. When targeting a brain region for NIBS, it can be difficult to ensure activation of only target regions. Optimal Montages for cerebellar stimulation for pain modulation have not been established. This paper systematically examines cerebellar NIBS Montages by comparing simulated current flow models for targeted conventional cerebellar tDCS and focused high-definition 4 × 1 HD-tDCS, to examine the most effective Montage for targeting only the lobes of the cerebellum. The objective was to explore if slight variations in electrode placement and voltage could be producing confounding activations of other brain regions as shown by the Soterix® current modelling software (Ver. 2019). A left deltoid anode for right cerebellar lobe sponge (3 cm lateral to inion) produces the best targeting with conventional tDCS. For high-definition tDCS (HD-tDCS) a 4 × 1 array based on a 93-electrode EEG map, with the central electrode at PO10, and the array at O2, P8, Ex2, and Ex6, provided focal stimulation. Optimisation of NIBS must include an evaluation of electrode Montages and current flow modelling to determine which structures and pathways will be impacted by the neurostimulation. This approach is essential for future cerebellar NIBS experimental design and will facilitate comparative analysis across different protocols and optimise understanding of the role of the cerebellum in pain processing.